Analysis of surface ozone episodes using WRF-HYSPLIT model at Biga Peninsula in the Marmara region of Turkey - (:unkn) unknown (My University, 2020)
Ozone episodes were observed frequently in Biga Peninsula of Marmara region in Turkey which is suburban site and has forests and agricultural areas. This study aims to understand the role of atmospheric conditions that lead to the ozone episodes over the Biga Peninsula. Ozone concentrations were measured at the monitoring stations for three years (2013–2015) to identify and characterize the ozone episodes in the study area. HYSPLITv4 model driven by the WRF ARW v3.8 and surface data is used to identify the emission source locations. The WRF ARW results were analyzed for the meteorological variables used in the study (e.g. air temperature, relative humidity, u and v wind components) with index of agreement, correlation coefficient, mean bias error, and root mean squared error. It is found that local photochemical production and accumulation and transport of pollutants from the anthropogenic sources (residential, traffic and industrial) in Marmara regions are the most important factors on ozone levels. The five ozone episodes were also analyzed using HYSPLIT model to infer long range transport. Three-day backward air mass trajectories analysis is performed to assess the contribution of long-range transport of pollutants, resulting in the following main routes: Istanbul and Black Sea. The results show that rural areas have higher cumulative exposure to ozone than suburban locations.